Whole farm economic evaluation of East Coast fever immunization strategies on farms in the Uasin Gishu District of Kenya - Nyangito, H.O.; Richardson, J.W.; Mukhebi, A.W.; Mundy, D.S.; Zimmel, P.; Namken, J. (Elsevier, 1995)
East Coast fever (ECF) is a major constraint limiting livestock production in Eastern, Central, and Southern Africa. The infection and treatment method (ITM) has proven effective in research station and field trials. The work described in this paper was to quantify the economic payoffs to case study farms that adopt alternative ITM strategies and current ECF control methods. A whole farm simulation model was used to estimate the financial and economic payoffs to ITM and to estimate the probability distribution of returns for alternative ECF control strategies. Stochastic dominance was used to rank the alternative ECF controls for risk average decision makers. The whole farm simulation model used for the analysis has the advantage of incorporating risk aspects involved in farm production, and ranking alternative strategies, as well as estimating the farmer's premium for risk preference associated with alternative ECF control strategies.